2007
DOI: 10.1063/1.2437659
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced magnetocaloric response in Cr∕Mo containing Nanoperm-type amorphous alloys

Abstract: The magnetocaloric effect of Fe76Cr8−xMoxCu1B15 (x=0,4) alloys is studied. Although the combined addition of Cr and Mo is more efficient in tuning the Curie temperature of the alloy, the Mo-free alloy presents a higher magnetocaloric response. The refrigerant capacity (RC) for the Mo-containing alloy is comparable to that of Gd5Ge1.9Si2Fe0.1 (for a field of 50kOe, RC=273Jkg−1 for the Mo alloy vs 240Jkg−1 for the Gd-based one), with a larger temperature span of the optimal refrigeration cycle (250K vs 90K, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Metallic glasses undergo a second order magnetic transition and exhibit a broadened magnetic entropy change peak. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Therefore, although the peak values of magnetic entropy change (-∆S m peak ) for the metallic glasses are not as high as some of the crystalline alloys, the amorphous alloys still have evoked intensive interests because their refrigeration capacity (RC) are usually several times higher than that of the crystalline alloys. Our recent results have shown that the RC can reach an ultra-high value of above 800 J·kg −1 under 5 T, accompanied with a relatively high -∆S m peak value of nearly 10 J·kg −1 ·K −1 under 5 T in some of the Gd-based metallic glasses.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Metallic glasses undergo a second order magnetic transition and exhibit a broadened magnetic entropy change peak. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Therefore, although the peak values of magnetic entropy change (-∆S m peak ) for the metallic glasses are not as high as some of the crystalline alloys, the amorphous alloys still have evoked intensive interests because their refrigeration capacity (RC) are usually several times higher than that of the crystalline alloys. Our recent results have shown that the RC can reach an ultra-high value of above 800 J·kg −1 under 5 T, accompanied with a relatively high -∆S m peak value of nearly 10 J·kg −1 ·K −1 under 5 T in some of the Gd-based metallic glasses.…”
mentioning
confidence: 99%
“…This proposition was subsequently confirmed with experimental results for other amorphous alloys. 18,23 Figure 3 shows the master curve behavior of the magnetic entropy change curves of the studied alloys. This confirms, for this particular alloy series, the predictions of a master curve behavior for different alloy compositions of the same series.…”
Section: Resultsmentioning
confidence: 99%
“…8 More recently, soft magnetic amorphous alloys are getting increasing attention as low-cost candidates for magnetic refrigeration. [9][10][11][12][13][14][15][16][17][18] ͑According to a well-known bibliographic database, more than 36% of the literature on the magnetocaloric effect in amorphous materials were published since 2005. Considering only the magnetocaloric effect in transition-metal-based amorphous alloys, more than 50% of the papers studying these materials were published since then.͒ Although the maximum magnetic entropy change, ͉⌬S M pk ͉, for these alloys is modest when compared to that of rare-earth-based materials, 1,6 the remarkable difference in material costs is an incentive for studying their suitability as magnetic refrigerants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have focused on magnetocaloric materials with amorphous or nanocrystalline structure [1][2][3][4]. One of the most typical materials is amorphous alloys.…”
Section: Introductionmentioning
confidence: 99%